Do monetary unions dream of structural reforms? - Christopher Loewald; Andreas Wörgötter (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2019)
When the principal decisions for the European Monetary Union (EMU) were made it was acknowledged that it would not be an optimal currency area (OCA). Potential trouble was assumed away as asymmetric shocks were expected to fade, while rising productivity enhanced the resilience of EMU member economies. We argue however that for less export-focused member countries the loss of the exchange rate mechanism has become an especially debilitating constraint limiting recovery from recessions. The common monetary policy helps to absorb some financial shocks but cannot address structural issues in financial, product or labour markets. Fiscal policy too is constrained. It has little positive short-run impact on competitiveness and works as a shock absorber only if fiscal balances are sustainable. Without nominal exchange rate adjustments, only internal devaluation corrects an overvalued real exchange rate, either through wage restraint or productivity increases. Co-ordinated sets of prioritised structural policies could push the real exchange rate in the right direction and generate cross-border synergies, reducing short run costs. For example, Germany should lower its value added tax (VAT) to provide room for more imports, while Italy and other deficit economies could strengthen work incentives to reduce labour shortages in the export sector.
Keywords: 330